JOB AMBIGUITY ON THE PROBABILITY OF LABOUR TURNOVER AT BPR SYARIAH BUANA MITRA PERWIRA PURBALINGGA - Rizka Rayhana Burhan; Andi Aris Mattunruang, Dilllah Faradilla Hasanah, Riski Aprilianti Baharuddin, Andi Izatul Fiddah (Adisam Publisher, 2024)
BPR Syariah Buana Mitra Perwira is one of the Regional Owned Enterprises (BUMD) of Purbalingga Regency engaged in the financial sector. In the BPR Syariah Buana Mitra Perwira environment, task complexity and unclear job roles can create a situation of job ambiguity that has the potential to affect workforce stability. This study aims to determine the contribution of job ambiguity to the probability of turnover at BPR Syariah Buana Mitra Perwira. The study used a qualitative method with descriptive analysis of 10 employees from the results of random sampling techniques with observation and interview methods using a questionnaire. The results showed that on average 62% of employees stated that there was job ambiguity, while 38% of employees stated otherwise. In addition, the results of the probability of turnover in the high category are 8.7%. The research can be concluded that there is an influence of job ambiguity on the probability of labour turnover along with influencing factors in company policies and practices. The practical implications of these findings can support organisations in designing more efficient management policies and practices to maintain and improve employee satisfaction and workforce stability.